Functions of MnOx in NaCl Aqueous Solution for Artificial Photosynthesis - Sayuri Okunaka; Yugo Miseki; Kazuhiro Sayama (iScience, 2020)
Summary: Photoelectrochemical water splitting has been intensively investigated as artificial photosynthesis technology to convert solar energy into chemical energy. The use of seawater and salted water has advantages for minimum environmental burden; however, the oxidation of Cl− ion to hypochlorous acid (HClO), which has toxicity and heavy corrosiveness, should occur at the anode, along with the oxygen evolution. Here, O2 and HClO production in aqueous solution containing Cl− on photoanodes modified with various metal oxides was investigated. The modification of MnOx resulted in the promotion of the O2 evolution reaction (OER) specifically without HClO production over a wide range of conditions. The results will contribute not only to the practical application of artificial photosynthesis using salted water but also to the elucidation of substantial function of manganese as the element for OER center in natural photosynthesis.